Design of wood structures ASD - Breyer, Donald E. (McGraw Hill, 1998)
Wood buildings and design criteria; Design loads; Behavior of structures under loads and forces; Properties of wood and lumber grades; Structural glued laminated timber; Beam design; Axial forces and combined bending and axial forces..